Evaluation of the i-STAT Alinity v in a veterinary clinical setting. (July 2021) - Burke, Jasper E.; Nguyen, Thuy Hien T.; Davis, Tanya; Koenig, Amie; Lane, Selena L.; Good, Jennifer; Brainard, Benjamin M.
Many point-of-care (POC) analyzers are available for the measurement of electrolytes and acid-base status in animals. We assessed the precision of the i-STAT Alinity v, a recently introduced POC analyzer, and compared it to 2 commonly used and previously validated POC analyzers (i-STAT 1, Stat Profile pHOx Ultra). Precision was evaluated by performing multiple analyses of whole blood samples from healthy dogs, cats, and horses on multiple i-STAT Alinity v analyzers. For comparison between analyzers, whole blood samples from dogs and cats presented to the emergency room were run concurrently on all 3 POC instruments. Reported values were compared by species (dogs and cats only) using Pearson correlation, and all values from all species were analyzed together for the Bland–Altman analysis. Results suggested that the i-STAT Alinity v precision was very good, with median coefficients of variability <2.5% for all measured parameters (except the anion gap), with variable ranges of coefficients of variation. In addition, good-to-excellent correlation was observed between the i-STAT Alinity v and i-STAT 1, and between the i-STAT Alinity v and Stat Profile pHOx Ultra for all parameters in both cats and dogs, respectively. In this cohort, the i-STAT Alinity v had clinically acceptable bias compared to the currently marketed analyzers and can be used for monitoring measured analytes in cats and dogs, although serial measurements in a single animal should be performed on the same analyzer whenever possible.